Digital Curation Education and Training: From Digitization to Graduate Curricula to MOOCs - Helen R. Tibbo (International Journal of Digital Curation, 2015)
This paper traces the development of digital and data curation curricula. Due to the brief length of this paper, the focus is on North American initiatives and primarily on continuing education programs. It explores the strengths and weaknesses of professional workshops and the creation of graduate-level courses, certificates, degrees and MOOCs, as well as the role of funding agencies in this process. It concludes with an analysis of what is missing and what is needed to create the workforce required to steward digital assets in the foreseeable future.